Assessment of source contributions to seasonal vegetative exposure to ozone in the U.S. Issue 1 (14th January 2014) - Lapina, Kateryna; Henze, Daven K.; Milford, Jana B.; Huang, Min; Lin, Meiyun; Fiore, Arlene M.; Carmichael, Greg; Pfister, Gabriele G.; Bowman, Kevin
<x xml:space="preserve">Abstract</x> [1] W126 is a cumulative ozone exposure index based on sigmoidally weighted daytime ozone concentrations used to evaluate the impacts of ozone on vegetation. We quantify W126 in the U.S. in the absence of North American anthropogenic emissions (North American background or "NAB") using three regional or global chemical transport models for May–July 2010. All models overestimate W126 in the eastern U.S. due to a persistent bias in daytime ozone, while the models are relatively unbiased in California and the Intermountain West. Substantial difference in the magnitude and spatial and temporal variability of the estimates of W126 NAB between models supports the need for a multimodel approach. While the average NAB contribution to daytime ozone in the Intermountain West is 64–78%, the average W126 NAB is only 9–27% of current levels, owing to the weight given to high O3 concentrations in W126. Based on a three‐model mean, NAB explains 30% of the daily variability in the W126 daily index in the Intermountain West. Adjoint sensitivity analysis shows that nationwide W126 is influenced most by NOx emissions from anthropogenic (58% of the total sensitivity) and natural (25%) sources followed by nonmethane volatile organic compounds (10%) and CO (7%). Most of the influence of anthropogenic NOx comes from the U.S. (80%), followed by Canada (9%), Mexico (4%), and China (3%). Thus, long‐range transport of pollution has a relatively small impact on W126 in the U.S., and domestic emissions control should be effective for reducing W126 levels.